(untitled) - George, James David (Boston, 1994)
Introduction to exercise science, muscular fitness, flexibility, heart rate and blood pressure...
Keywords: Exercise,Physical education and training,Muscle strength,Rèn luyện,Sức mạnh cơ bắp,Giáo dục và đào tạo thể chất